Allelopathy on estates crops and its control techniques and utilization prospects - DJAZULI, MUHAMAD (Perspektif, 2011)
Soil fertility is an important factor of abiotic growth environment on growth and production. Soil fertility it self is influenced by macro and micronutrient status and toxic compound in the soil. Once of toxic compound released by plant and it can affect other plant growth and their growth it self. Information of allelopathy in estate crps are limited. Allelopathyc compounds are released from the plant as root exudate, vapour from leaf in a gas form through stomata, foliar leacheate, decomposition product of dead plant parts, and microorganism tranformation. For example, a significantly decreased of ginger and patchouli productivity at second cultivation at fertile soil and no pest attack, indicated that ginger and patchouli released autotoxic allelopathy compound. Arabica coffee released 1.3.7-trimethylxanthin com-pound that is potentially inhibit lettuce germination and also produce autotoxic allelopathy compound of caffeine. It was found some alleloptathy compounds produced by patchouli such as coumaric acid, hydroxi benzoic acid, adific acid, and sinapic acid. Application of liming, active carbon, Salicilic acid, MgSO.7 H2O, soil micoorganism, and rotation system using aromatic plant especialy, mint, basil, sage and oregano were able to reduce allelopathy compound and improved productivity of land and plant. It was reported that some allelopathic compounds can be utilized as a potentially organic herbicide. Key words: Allelopathy, estate crops, management, growth inhibitor, organic herbicide